50 + 4 * { 12 + 2 * [ 300 -6 * ( 45 - 3 * 7 + 2 la puretea 3 ]}
Răspunsuri la întrebare
Răspuns de
11
Răspuns: 962
Explicație pas cu pas:
Salutare!
50 + 4 × { 12 + 2 × [ 300 - 6 × ( 45 - 3 × 7 + 2³]} =
50 + 4 × { 12 + 2 × [ 300 - 6 × ( 45 - 21 + 8]} =
50 + 4 × [12 + 2 × ( 300 - 6 × 32)] =
50 + 4 × [12 + 2 × ( 300 - 192)] =
50 + 4 × (12 + 2 × 108) =
50 + 4 × (12 + 216) =
50 + 4 × 228 =
50 + 912 =
962
==pav38==
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Ed. muzicală,
8 ani în urmă
Engleza,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă